Blood Urea Nitrogen-to-Albumin Ratio in Predicting Long-Term Mortality in Patients Following Coronary Artery Bypass Grafting: An Analysis of the MIMIC-III Database - Zhao, Diming; Chen, Shanghao; Liu, Yilin; Xu, Zhenqiang; Shen, Hechen; Zhang, Shijie; Li, Yi; Zhang, Haizhou; Zou, Chengwei; Ma, Xiaochun (Frontiers in Surgery, 2022)
Background: This study examined the role of blood urea nitrogen to albumin ratio (BAR) in predicting the long-term mortality in patients undergoing coronary artery bypass grafting (CABG). Methods: In this retrospective cohort study, patients undergoing CABG were enrolled from the Medical Information Mart for Intensive Care III (MIMIC III) database. Patients were divided into three groups according to the optimal cut-off values of BAR determined by X-tile software. Survival curve was constructed by Kaplan-Meier method and multivariable Cox regression analysis was performed to explore the independent prognostic factors of one- and four-year mortality after CABG. And receiver operating characteristic (ROC) curves and areas under the ROC curves (AUCs) were calculated to estimate the accuracy of BAR in predicting the outcomes. Subgroup analyses were also carried out. Results: A total of 1462 patients at four-year follow-up were included, of which 933, 293 and 236 patients were categorized into the group 1 (≤6.45 mg/g), group 2 (>6.45 mg/g and ≤10.23 mg/g) and group 3 (>10.23 mg/g), respectively. Non-survivors showed an increased level of BAR at both one- (p<0.001) and four-year (p<0.001) follow-up compared to survivors. The patients with a higher BAR had a higher risk of one- and four-year mortality following CABG (33.05% vs 14.33% vs 5.14%, p<0.001 and 52.97% vs 30.72% vs 13.08%, p<0.001, respectively). Cox proportional hazards regression model suggested a higher BAR as an independent risk factor of one-year mortality (HR 3.904; 95% CI 2.559-5.956; P<0.001) and four-year mortality (HR 2.895; 95% CI 2.138-3.921; P<0.001) after adjusting for confounders. Besides, the receiver operating characteristic (ROC) curves showed better predictive ability of BAR compared to other grading scores at both one- (0.7383, 95% CI: 0.6966-0.7800) and four-year mortality (0.7189, 95% CI: 0.6872-0.7506). Subgroup analysis demonstrated no heterogeneous results of BAR in four-year mortality in particular patient groups. Conclusions: This report provided the evidence of an independent association between one- and four-year mortality after CABG and BAR. A higher BAR was associated with a higher risk of long-term mortality, and could serve as a prognostic predictor in patients following CABG.